Squalus acanthias Linnaeus 1758 - Ebert, David A.; Wintner, Sabine P.; Kyne, Peter M. (Zenodo, 2021)
Squalus acanthias Linnaeus, 1758 Spiny Dogfish Squalus acanthias Linnaeus, 1758: 233. Syntypes: NRM 85 (1 or 2). Possible Syntypes: ZMUU Linn. Coll. 159 (1), ZMUU, Linn. Coll. 160 (1, dry). Type locality: Mediterranean Sea and northeastern Atlantic [original: “Habitat in Oceano Europaeo”]. Local synonymy : Squalus vulgaris : Bleeker, 1860b: 57; Thompson, 1914: 149. Squalus acanthias : Gilchrist, 1922b: 48; Barnard, 1925: 36; Smith, 1949a: 60, fig. 64; Smith, 1965: 60, fig. 64; Bass et al ., 1976: 13, figs. 6a, 8e–g, 9, pl. 1; Compagno, 1984a: 111, fig.; Bass et al ., 1986: 61, fig. 5.24; Compagno et al ., 1989: 22, pl.; Compagno et al ., 1991: 66; Ebert et al ., 1992: 606; Compagno, 1999: 114; Heemstra & Heemstra, 2004: 54; Compagno et al ., 2005: 73, fig., pl. 3; Ebert et al ., 2013 a: 83, fig., pl. 4; NPOA, 2013: 39; da Silva et al ., 2015: 248; Ebert, 2015: 58, fig. 60; Ebert & Mostarda, 2015: 17, fig.; Ebert & van Hees, 2015: 144; Compagno, 2016: 1159; Weigmann, 2016: 902. Squalus acanthias africana : Myagkov & Kondyurin, 1986: 5 (described from “Wolffish Bay”, but co-ordinates [28°S, 17°E] indicate Port Nolloth, South Africa rather than Walvis Bay, Namibia). South Africa voucher material : SAIAB 4195, SAIAB 6034, SAIAB 6035, SAIAB 7829, SAIAB 8014, SAIAB 21873, SAIAB 21874, SAIAB 21875, SAIAB 21876, SAIAB 21877, SAIAB 21878, SAIAB 25312, SAIAB 25313, SAIAB 25314, SAIAB 25315, SAIAB 25316, SAIAB 25317, SAIAB 25318, SAIAB 25319, SAIAB 25320, SAIAB 25325, SAIAB 25326, SAIAB 25327, SAIAB 25706, SAIAB 25719, SAIAB 25918, SAIAB 26300, SAIAB 26301, SAIAB 26302, SAIAB 27168, SAIAB 40864, SAIAB 48524, SAIAB 63974, SAIAB 201576. South Africa distribution : Port Nolloth to Cape Point (WC) and possibly to Port Alfred, (EC). Remarks : Off the west coast of South Africa this is an offshore species of the outer shelf and upper slope that appears to occupy a relative narrow range, mostly between 150–400 m depth and from Port Nolloth to Cape Point (Compagno et al ., 1991). Records of it along the south coast ...